2011
DOI: 10.20430/ete.v78i309.27
|View full text |Cite
|
Sign up to set email alerts
|

La política de estímulos fiscales a ID en México. Alcances limitados en el contexto de innovación de las empresas

Abstract: Taking as point of departure the basics of the economics of innovation, the Mexican evidence builds on two major obstacles: market failures inhibit economic returns to R&D and, consequently, the inexistence of a national innovation system. In such context, fiscal subsidies to R&D are introduced with limited success. The fiscal subsidies remain highly concentrated in a few very large firms, in mature sectors for minor product and process innovations. Most of these are global firms and their R&D response are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…En general, los resultados confirman la mayor importancia que reviste el sector más relacionado con el uso de capital productivo para innovar, además de que son consistentes con la hipótesis de efectos diferenciados no sólo entre regiones, sino también entre sectores de la actividad económica, un aspecto que, en el caso mexicano, es importante distinguir para enfocar una adecuada política de innovación (Unger, 2011).…”
Section: Resultsunclassified
“…En general, los resultados confirman la mayor importancia que reviste el sector más relacionado con el uso de capital productivo para innovar, además de que son consistentes con la hipótesis de efectos diferenciados no sólo entre regiones, sino también entre sectores de la actividad económica, un aspecto que, en el caso mexicano, es importante distinguir para enfocar una adecuada política de innovación (Unger, 2011).…”
Section: Resultsunclassified
“…This has been made evident by some analysis of the use of policy instruments in countries of the region. In Mexico, for example, an analysis of fiscal incentives for innovation (a typically market-friendly, horizontal policy tool) revealed that main beneficiaries over time have always been the same large foreign corporations and that these incentives had very limited impact in terms of fostering systemic learning and innovation in industrial clusters in Mexico (Sánchez and Poy, 2019;Unger, 2011).…”
Section: Industrial Policies Struggle To Be Pivotal In National Develmentioning
confidence: 99%
“…Asimismo, la bibliografía de innovación ha reconocido ampliamente que se requiere de una correcta aplicación para ser efectiva. Como mostramos en otro artículo, la evidencia mexicana, al poner en práctica los estímulos fiscales a la I&D, no permitía dar por buena tal condición de efectividad(Unger, 2011).…”
unclassified